The Strategy of Organic Fertilizer Production System Development on Organic Fertilizer Processing Unit (UPPO) in Bangunsari Village, Ciamis - Sardjono, Nurihyatun; Susilo, Bambang; Wignyanto, Wignyanto (Fakultas Teknologi Pertanian Universitas Brawijaya, 2012)
The purpose of this study to determine strategies for developing appropriate production system on UPPO in the Village Bangunsari. This study uses AHP and the data was processed using Expert Choice software. Based on survey results revealed that the main factors to consider in the development of UPPO is well within the knowledge of farmers using fertilizers and in processing. The actor who plays a role in increasing farmers’ knowledge is government and UPPO managers. Priority target system development is the increase in farmers’ income. To support the achievement of this target is selected developing UPPO policy. Based on the identification of factors, actors, objectives and policies of the development strategy of organic fertilizer production systems in UPPO at the village Bangunsari is local government managers need to conduct an intensive outreach program to increase the knowledge of farmers on the use of waste straw so that the development of organic fertilizer production systems at UPPO can be done gradually and eventually the farmer’s income can also be increased. Keywords: potency, waste, rice straw, farmer